Dynamic behaviour model of permanent magnet synchronous motor fed by PWM inverter and fuzzy logic controller for stator phase current, flux and torque control of PMSM - (:unkn) unknown (IEEE, 2001)
In this paper, fuzzy logic controller is designed to obtain the desired output torque, stator phase current and stator flux of permanent magnet synchronous motor(PMSM) fed by a current-controlled PWM(Power-Width-Modulated) inverter which is built using six MOSFET(Metal-Oxide-Semiconductor-Field-Effect-Transistor). Model of PMSM is established using the equations describing dynamic behavior of permanent magnet synchronous motor in Matlab-Simulink program respectively. In this study, at the same time, fixed-gain PI controller was used to control stator phase current, stator flux and torque value of PMSM. Moreover, a comparison between the conventional fixed-gain PI controller and fuzzy logic controller is presented. After controlling the systems both PI and Fuzzy Logic it is seen clearly that Fuzzy Logic control is reasonably better result and performance than PI controller.